2005
DOI: 10.1161/01.hyp.0000165678.63373.8c
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Selectively Improves Large Elastic Artery Compliance in Postmenopausal Women

Abstract: Abstract-The compliance of large elastic arteries in the cardiothoracic region decreases with advancing age/menopause and plays an important role in the increased prevalence of cardiovascular diseases in postmenopausal women. We determined whether oxidative stress contributes to the reduced large elastic artery compliance of postmenopausal women. Carotid artery compliance was measured during acute intravenous infusions of saline (baseline control) and supraphysiological doses of the potent antioxidant ascorbic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 62 publications
8
70
0
Order By: Relevance
“…[5][6][7]13,25 Our finding that plasma oxidized LDL concentrations, a systemic marker of oxidative stress, 26 were greater in older men is in agreement with previous observations from our laboratory in similarly healthy, well-screened men and postmenopausal women. 5,20 The present results extend these findings by providing direct evidence of oxidative stress in ECs from older adults. Specifically, we found that nitrotyrosine, which reflects nitration of tyrosine residues on proteins 27 and, thus, serves as an indicator of oxidative stress, 28 is elevated in ECs collected from the brachial artery and peripheral veins of older compared with young healthy men.…”
Section: Aging and Ec Oxidative Stresssupporting
confidence: 85%
See 1 more Smart Citation
“…[5][6][7]13,25 Our finding that plasma oxidized LDL concentrations, a systemic marker of oxidative stress, 26 were greater in older men is in agreement with previous observations from our laboratory in similarly healthy, well-screened men and postmenopausal women. 5,20 The present results extend these findings by providing direct evidence of oxidative stress in ECs from older adults. Specifically, we found that nitrotyrosine, which reflects nitration of tyrosine residues on proteins 27 and, thus, serves as an indicator of oxidative stress, 28 is elevated in ECs collected from the brachial artery and peripheral veins of older compared with young healthy men.…”
Section: Aging and Ec Oxidative Stresssupporting
confidence: 85%
“…Plasma samples were analyzed for oxidized low-density lipoprotein, a marker of systemic oxidative stress, and serum samples were analyzed for total antioxidant status, a measure of systemic antioxidant defenses, as previously described. 20 Serum concentrations of C-reactive protein were measured using a high-sensitivity ELISA (Olympus AU400e Chemistry Analyzer and reagents). Dietary intake of macro-and micronutrients was estimated from 4-day diet records as described previously.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…Several conventional and nonconventional risk factors for CVD change with age, even in healthy adults (9,10,14,23), as was the case in the present study (Table 1). However, these factors were not significant predictors of the age-associated MCP-1, B), and interleukin-6 (IL-6, C) in peripheral blood mononuclear cells from sedentary (Sed) young and older adults (n ϭ 8 -14/group).…”
Section: Expression Of Proinflammatory/-oxidative Genes In Pbmc Of MIsupporting
confidence: 75%
“…Fasting circulating metabolic factors were determined by standard assays at the CTRC core laboratory. Plasma samples were analyzed for oxidized low-density lipoprotein (LDL), a marker of systemic oxidative stress, and serum samples were analyzed for total antioxidant status, as previously described (23). Serum concentrations of the inflammatory markers C-reactive protein (CRP), TNF-␣, and IL-6 were measured as previously described (9).…”
Section: Study Proceduresmentioning
confidence: 99%
“…Nrf-2, the master transcription factor that regulates antioxidant genes, is protective in maternal diabetes-induced perinatal hypertension (30,221). Antioxidant vitamins reduced blood pressure and arterial stiffness in patients with diabetes (240), but had no effect in postmenopausal women or in healthy subjects (140). Population studies have demonstrated an inverse association between plasma vitamin C levels and vitamin C consumption with blood pressure (28,139), and a recent meta-analysis reported that vitamin C supplementation reduced systolic and diastolic blood pressure (147).…”
Section: Ros Oxidative Stress and Human Hypertensionmentioning
confidence: 99%